Cardiorespiratory fitness and physical function in children with cancer from diagnosis throughout treatment. Issue 1 (12th May 2017) - Thorsteinsson, Troels; Larsen, Hanne Baekgaard; Schmiegelow, Kjeld; Thing, Lone Friis; Krustrup, Peter; Pedersen, Mogens Theisen; Christensen, Karl Bang; Mogensen, Pernille Rudebeck; Helms, Anne Sofie; Andersen, Lars Bo
Abstract : Background: Children with cancer experience severe reductions in physical fitness and functionality during and following intensive treatment. This may negatively impact their quality of life. Purpose: To describe the physical capacity and functionality of children with cancer during and after treatment as well as the feasibility of physical activity intervention in the Rehabilitation including Social and Physical activity and Education in Children and Teenagers with Cancer study. Patients and methods: The study included children diagnosed from January 2013 to April 2016 with paediatric cancer or Langerhans cell histiocytosis, all treated with chemotherapy. Seventy-five of 78 consecutively eligible children (96.2%) were included. Median age was 11 years (range 6‒18). The physical capacity and function were assessed based on testing of physical strength, balance and cardiorespiratory fitness. Children were tested at diagnosis, 3 and 6 months after diagnosis and 1 year after cessation of treatment. The feasibility evaluation was inspired by the criteria for reporting the development and evaluation of complex interventions in healthcare. Results: All children participated in the physical intervention programme with no dropouts. Strenuous physical exercise and physiological testing during paediatric cancer treatment was safe and feasible, with only five minor adverse events during the intervention. Cardiorespiratory fitness was significantly lower in children with cancer than norms for healthy age-matched children at diagnosis (difference 19.1 mL/kg/min, 95% CI 15.4 to 22.7; p <0.0001), during treatment 3 and 6 months from diagnosis (difference 21.0 mL/kg/min, 95% CI 17.4 to 24.6; p <0.0001 and difference 21.6 mL/kg/min, 95% CI 17.3 to 25.8; p <0.0001, respectively) and 1 year after cessation of treatment (difference 6.9 mL/kg/min, 95% CI 1.1 to 12.7; p <0.0072). Furthermore, children with cancer experienced a pronounced decline in physical function. Conclusion: This study shows that it is safe and feasible to perform strenuous physical exercise and testing during paediatric cancer treatment and that children with cancer have significantly lower physical capacity and functionality than healthy age-matched norms. Trial registration number: ClinicalTrials.gov: NCT01772862 .